(3JMaI GdWdGH HTQM JMQjQ JfbjM GddHGHs - (3GdSfjcj, GdeUQj, GdTGaYqj, CHh jMji, TjN GdESdGe, RcQjG Hf eMeO Hf CMeO Hf RcQjG, J (B926 (3g`s
(3ChdgG (B:s
- (3aj GdHGH GdSGHb hjTJQW aj GdLejY GdESdGe HGH GdcaGQI (B: (3eCNhP ef GdcaQ HaJM GdcGa hgh GdSJQ dCfgG JSJQ GdPfhH hgj CQHYI caGQI XgGQs
(3BNQgG (B:s
(3hCMO CUhdg eSde (B((3aeSde(B) (3JHYG hGdESdGe jYdh hPcQ gPG ef RjGOJj hdh cGf CMO CHhjg eQJOG hGdBNQ cGaQ CUdj acGaQ CUdj bGdg GdHZhj hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 46s
(3eYLe GdeDdajf (B1 / 733s
(3cTa GdXfhf (B2 / 1542s
(3TPQGJ GdPgH (B8 / 134s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs